(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article explores effective approaches to teaching writing in non-philological higher educational institutions, with a focus on the context of English language instruction. Writing proficiency is a crucial skill for students in diverse disciplines, and it requires tailored instructional strategies to meet their specific needs. The article discusses various methods and strategies that instructors can employ to enhance the teaching of writing. These include utilizing authentic materials, developing research skills, fostering language awareness, promoting peer collaboration, integrating technology tools, and creating a supportive writing community. Additionally, the article emphasizes the importance of addressing common writing challenges, cultivating critical thinking skills, and connecting writing to real-world applications. By implementing these approaches, instructors can empower students to become proficient and confident writers in English across academic and professional contexts.